2022
DOI: 10.3390/genes13112030
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Methylation of NRF1, FTO, and LEPR Gene in Childhood Obesity

Abstract: Childhood obesity has affected the health of millions of children around the world despite vigorous efforts by health experts. The obesity epidemic in the United States has disproportionately afflicted certain racial and ethnic minority groups. African American children are more likely than other children to have obesity-related risk factors such as hyperlipidemia, diabetes, cardiovascular disease, and coronavirus disease (COVID-19). For the reduction in obesity-related health inequalities to be successful, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…TAB2 [131], CCR4 [112], LTF (lactotransferrin) [126], hsa-mir-146a-5p [613], hsa-mir-8485 [614], BRCA1 [615], NFKB1 [616], TEAD1 [617], TFAP2C [618], FOXO3 [619 and NRF1 [620] risk factors have been shown to increase susceptibility to cardiovascular diseases. Several studies have shown that TAB2 [131], LTF (lactotransferrin) [487], BRCA1 [621], NFKB1 [622], TEAD1 [623], FOXO3 [624] and NRF1 [625] can be involved in the disease progression of obesity ., Altered expression of CCR4 [280], LTF (lactotransferrin) [295], CDH1 [313], CFTR (CF transmembrane conductance regulator) [317], hsa-mir-146a-5p [626], hsa-mir-195-5p [627], hsa-mir-4739 [628], HNF4A [629], NFKB1 [630], NR2F1 [631], FOXO3 [632] and NRF1 [633] are observed in diabetes mellitus. CCR4 [407], hsa-mir-146a-5p [634] and NFKB1 [635] were associated with psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…TAB2 [131], CCR4 [112], LTF (lactotransferrin) [126], hsa-mir-146a-5p [613], hsa-mir-8485 [614], BRCA1 [615], NFKB1 [616], TEAD1 [617], TFAP2C [618], FOXO3 [619 and NRF1 [620] risk factors have been shown to increase susceptibility to cardiovascular diseases. Several studies have shown that TAB2 [131], LTF (lactotransferrin) [487], BRCA1 [621], NFKB1 [622], TEAD1 [623], FOXO3 [624] and NRF1 [625] can be involved in the disease progression of obesity ., Altered expression of CCR4 [280], LTF (lactotransferrin) [295], CDH1 [313], CFTR (CF transmembrane conductance regulator) [317], hsa-mir-146a-5p [626], hsa-mir-195-5p [627], hsa-mir-4739 [628], HNF4A [629], NFKB1 [630], NR2F1 [631], FOXO3 [632] and NRF1 [633] are observed in diabetes mellitus. CCR4 [407], hsa-mir-146a-5p [634] and NFKB1 [635] were associated with psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information of the study participants has been previously given in Patel et al [ 34 ]. Briefly, children aged 6 to 10 years were recruited from Lee and Macon counties, AL.…”
Section: Methodsmentioning
confidence: 99%
“…The multiplex PCR was carried out for the three genes NRF1 , FTO , and LEPR , for which two primers and one probe for each gene were designed. Detailed protocols for each step have been mentioned in previous published article [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cap ‘n’ collar-basic leucine zipper protein (CNC-bZIP) nuclear factor erythroid 2-related factor 1 (NFE2L1, also known as NRF1) is a master regulator controlling the transcription of a suite of genes involved in proteasomal homeostasis, cell metabolism and numerous stress responses, antioxidant response in particular [ [8] , [9] , [10] , [11] ]. A single nucleotide polymorphism (SNP), rs3764400, in the 5′-flanking region of the human NFE2L1 gene, appears to be associated with obesity in humans [ [12] , [13] , [14] , [15] ]. In addition, an epigenome-wide association study identified human NFE2L1 as one of the genes nearest to the sentinel methylation markers of a locus linked to BMI and adverse outcomes of obesity [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%